L'interprétation arbitrale du contrat de commerce international - Arfaoui, Besma (Université de Limoges, 2008)
En interprétant le contrat, l'arbitre du commerce international a forgé un certain nombre de principes généraux qui consolident l'édification d'un corps de normes spécifiques au besoin de la communauté internationale des commerçants. Les principes généraux de la lex mercatoria font de l'arbitre une source de droit objectif. A ce premier volet sur lequel débouche l'approche interprétative de l'arbitre s'ajoute le second aspect de l'apport de l'interprétation du contrat. Ce second aspect met en exergue le rôle de l'arbitre en tant que source de droits subjectifs attachée à la détermination des prérogatives et des obligations respectives des parties. A travers cette détermination s'ouvre le débat relatif à l'étendue du pouvoir de l'arbitre à l'égard du contrat. La dimension créative de l'arbitre s'accentue à travers un contrôle restreint des juridictions étatiques. Ce contrôle fait de la sanction de la dénaturation commise par l'arbitre et de la révision au fond de la sentence des interdits à ne pas franchir. Interpreting the contract, the arbitrator of international commerce built up a number of general principles that consolidate the building of standards specific to the needs of the traders' international community. The general principles of Lex Mercatorea make of the arbitrator an objective law source. In addition to this constituent resulted by the interpretative approach of the arbitrator, there is the second aspect which the arbitration interpretation of the international commerce contract comes out with. This aspect highlights the role of arbitrator as a source of subjective laws, a role related to the determination of prerogatives and obligations respective to the parties. This determination leads to a debate relative to the range of powers of the arbitrator with regard to the contract. The creative dimension related to the interpretative approach of the arbitrator becomes more pronounced with the restricted control of state jurisdictions. This control controls the distortion committed by the arbitrator and the revision in the sentence of the proscription not to get over.
Keywords: Arbitrage; Arbitrage (droit international privé); Arbitragem; Arbitration; Commerce international; Commercial Law; Droit commercial; Droit international; International Trade; International law; Lex mercatoria

L'arbitrage et les tiers - Boularbah, Hakim; Caprasse, Olivier; Cox, Kristof; Dal, Marc; De Meulemeester, Dirk; Keutgen, Guy; Verbist, Herman; Wautelet, Patrick (Actes du colloque du CEPANI 40 du 28 novembre 2008, 2008)

L'expérience internationale de la Cour commune de justice et d'arbitrage de l'OHADA - Kenfack Douajni, Gaston (2è Congrès de l'Association des Hautes juridictions de cassation ayant en partage l'usage du Français (AHJUCAF), 2007)
Issu des actes du deuxième congrès de l'Association des Hautes juridictions de cassation ayant en partage l'usage du Français (AHJUCAF), Monsieur Gaston Kenfack-Douajni expose le bilan des activités de la Cour commune de justice et d'arbitrage de l'Ohada, ainsi que les actions susceptibles de renforcer son efficacité.
Keywords: Indépendance; Justice; Magistrature; OHADA

La clause de médiation - Huchet, Guillaume (Université Jean Moulin Lyon 3, 2007)
La clause de médiation est une stipulation qui a pour objet le règlement amiable des conflits apparaissant au cours de la vie d'un contrat. En ce sens, les parties contractantes s'obligent lors de la survenance d'un différend à mettre en oeuvre préalablement à toute action en justice, un processus de médiation, afin de trouver sous l'égide d'un médiateur une solution amiable. La clause de médiation est une stipulation originale, car elle a un objet duel à la fois contractuel et processuel. Elle comporte en effet un engagement de ne pas agir en justice et une obligation de négocier. Pour permettre une négociation utile, la clause de médiation suspend le droit d'action de chacune des parties. Toute action en justice exercée au mépris de cet engagement entraîne le prononcé d'une fin de non-recevoir ; l'action est dite prématurée. L'obligation de négocier peut se définir comme l'obligation par laquelle les parties s'engagent dans un premier temps à mettre en place le processus de médiation par la désignation d'un médiateur puis à conclure un protocole de mission. Elles devront ensuite s'efforcer de négocier, dans un esprit de bonne foi et de loyauté, une éventuelle solution amiable. Le processus de médiation prendra alors fin soit par la conclusion d'un accord de conciliation, généralement une transaction, soit par le constat d'un échec permettant alors aux parties de retrouver leur liberté d'agir en justice.
Keywords: Contrats; MARD; Mediación; Mediation; Mediação; Médiateur; Médiation; Procédure (droit); Règlement de conflits

La responsabilité de l'arbitre - Sorrente, Jean-Yves (Université Jean Moulin Lyon 3, 2007)
L'arbitrage est une institution de nature contractuelle. II est donc de coutume d'aborder les questions de responsabilité liées à cette activité sous l'angle exclusivement contractuel. Néanmoins, l'arbitre remplit une fonction juridictionnelle qui doit être préservée de toute interférence extérieure. De fait, la responsabilité de l'arbitre relève aussi bien du domaine disciplinaire, pénale, contractuel que délictuel. Aussi, l'étude de sa responsabilité doit-elle aborder ces différents aspects, tout en tenant compte de la nécessaire immunité dont doit bénéficier l'arbitre pour accomplir sa mission, sans pour autant jouir d'une totale impunité. Arbitration is a contractual institution. It is usual to approach questions of the arbitrator's responsibility only under the contractual aspect. Nevertheless, the arbitrator fills a jurisdictional function that must be preserved of exterior interference. The responsibility of the arbitrator concern just as well many domains: disciplinary aspect, criminal and civil liability. Also, the study of his responsibility must she approach these different aspects, all while taking account of the necessary immunity of which must profit the arbitrator to accomplish his mission, without for as much to enjoy a total impunity.
Keywords: Arbitrage; Arbitrage (droit); Arbitragem; Arbitration; Arbitres; Arbitres (droit); Immunité pénale; Responsabilité contractuelle; Responsabilité délictuelle

Waiver of a Right to Arbitrate by Resort to Litigation, in the Context of International Commercial Arbitration - Gillies, Peter; Dahdal, Andrew (Journal of International Commercial Law and Technology, 2007)
This paper examines the circumstances in which a party to an arbitration agreement may be deemed tohave waived its right to arbitrate a dispute comprehended by the agreement, by involvement in litigation concerning this dispute. The focus is on the law in common law jurisdictions, particularly Australia and theUnited States of America. United Kingdom law will also be briefly surveyed. The paper focuses on the 2006 decision of the Australian Federal Court in Comandate Marine Corp v Pan Australia Shipping Pty Ltd, whichafforded the topic significant treatment. The theoretical bases for sustaining waiver claims are analysed, includingwaiver as a discrete doctrine, abandonment, estoppel, election, repudiation of contract and variation of contract.The policies that underlie and inform the development of principles for testing waiver submissions are noted.

'Legal Traditions' and International Commercial Arbitration - Trakman, Leon (University of New South Wales, 2007)
Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration, the International Bar Association and the International Chamber of Commerce have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. More recent concerns have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it. Codes, laws and guidelines governing international commercial arbitration developed by such organizations as the International Court of Arbitration (ICA), the International Bar Association (IBA) and the International Chamber of Commerce (ICC) have been drafted against the background of Common Law and Civil Law values. In balancing these two great legal traditions, it was assumed that together they represent a composite legal tradition governing international commercial arbitration. The result of that assumption was decades of fine work enshrining international arbitration doctrines, principles, and rules of law and procedures that blend these two important legal traditions. From the doctrine of freedom of contract to specific rules of evidence and procedures that govern arbitral hearings, the international arbitration community has sought to maintain the respected legal traditions that lawyer-arbitrators and counsel find familiar and comfortable. More recent concerns, partly expressed by William K. Slate II, President of the American Arbitration Association, have begun to raise such questions as: How pervasive are the Common and Civil Law traditions? Are they sufficiently uniform in nature and operation to justify their dominant status in formulating codes, laws and rules governing international commercial arbitration? And has international commercial arbitration become unduly reliant upon both the Common and Civil Law traditions at the expense of other legal traditions that operate against the background of different and changing legal cultures? Part I of this article asks: What is a legal tradition and how should it be distinguished from a legal culture in relation to international commercial arbitration? Part II reflects on the influence of legal culture on international commercial arbitration. Parts III, IV and V investigate the Common and Civil legal traditions in relation to national, regional and international commercial arbitration. Part VI evaluates the public traditions that surround international commercial arbitration. Part VII considers whether change in the traditions of international commercial arbitration represent culture change or culture shock. Part VIII emphasizes the value of building an inclusive international arbitration tradition. Part IX suggests ways in which international commercial arbitration can accommodate diffuse and changing local, regional and global influences upon it.

Arbitrage et procès équitable dans la zone sud-ouest de l’Océan indien - Zattara-Gros, Anne-Françoise (Revue internationale de droit comparé, 2007)
L’étude des rapports qu’entretiennent l’arbitrage et le procès équitable dans les différents droits des îles de la zone sud-ouest de l’Océan indien prend toute sa dimension dès l’instant où la zone offre un patchwork de systèmes juridiques différents. La question est alors de savoir si dans les droits des îles des Grandes Mascareignes, l’arbitrage revêt le costume juridique français, sachant que le Nouveau Code de Procédure civile (NCPC) édicté en France le 5 décembre 1975 a été, suite à l’accession à l’indépendance de ces différentes pays, transplanté à Madagascar, aux Comores et à Maurice. La logique conduirait à répondre par l’affirmative. Mais la diversité du contexte, constitué soit de transposition du droit français de l’arbitrage, qui intègre le modèle de procès équitable notamment défini par l’article 6 de la Convention européenne des droits de l’homme, soit d’érection d’un droit interne de l’arbitrage composé partiellement de dispositions juridiques françaises, offre des situations inédites. Si à l’instar des grandes tendances, l’étude croisée des dispositions relatives à l’arbitrage et celles du procès équitable dans l’Océan Indien révèle une perméabilisation croissante de ce deux dernières sphères, et de là un risque de processualisation de l’arbitrage, l’institutionnalisation de l’arbitrage permet également aux parties, de trouver des garanties, ce qui est pleinement satisfaisant dans des pays où l’État de droit est défaillant et la justice étatique mise à mal de façon à assurer la sécurisation juridique des investissements et des échanges commerciaux. The study of reports stating that arbitration and fair judgment exist in the different laws of the islands in the south western zone of the Indian Ocean takes on a whole new dimension if the zone provides a patchwork of different legal systems. The question is whether or not arbitration is the same as in the French legal system. One must consider that the New Civil Procedure Code (NCPC) which was decreed in France on 5th December 1975, was transplanted to Madagascar, the Comoros Islands and Mauritius. Logic would thus lead one to believe the affirmative. However the diversity of the context, which is constituted either by transposing French arbitration law that integrates the decreed trial model as defined by article 6 of the European Convention of Human Rights, or the erection of internal arbitration law composed partially of French legal dispositions, provides some new situations. If, in accordance with the trends, the cross study of dispositions relative to arbitration and those of the fair trial in the Indian Ocean reveal that these two spheres are growing, and that a result of this there is a risk of procedure arbitration, the institutionalization of arbitration also allows for the concerned parties to find guarantees, which is very satisfying for countries whose state law is weak and where state justice has difficulty in ensuring legal security for investments and commercial exchange.

La problématique du consentement à l'arbitrage multipartite au sein des groupements de sociétés - Manirabona, Amissi Melchiade (Université de Montréal, 2006)
L'arbitrage étant une institution basée sur la volonté des parties, le consentement à la procédure arbitrale multipartite soulève de nombreuses questions relativement à la manière dont les parties expriment leur intention de faire partie d'une instance unique. Cette étude vise à déterminer les conditions dans lesquelles l'arbitre peut arriver à unifier la résolution des litiges qui impliquent les groupements de sociétés. Le plus naturel des moyens pour aboutir à une procédure multipartite est de prévoir cette possibilité à travers la convention d'arbitrage. Cela peut notamment provenir de la signature d'une convention d'arbitrage unique par toutes les parties concernées. Dans certains cas précis, l'arbitrage multipartite peut également résulter de plusieurs conventions d'arbitrage spécialement lorsque les parties participent à la réalisation d'un même ouvrage. Cependant, il arrive souvent qu'une partie qui n'a pas signé la convention d'arbitrage soit obligée à participer à l'instance. Même sans y être obligée, une partie non-signataire de la convention d'arbitrage peut aussi demander de participer à l'arbitrage pour défendre ses intérêts. Pour pouvoir admettre la participation à la procédure d'un tiers non-signataire de la convention d'arbitrage, les arbitres ont recours à plusieurs notions prévues par les droits internes. C'est ainsi que la levée du voile corporatif, la théorie de la réalité économique et le principe de l'estoppel constituent les meilleurs outils pour les arbitres d'amener à la procédure, par force ou sur demande, un non-signataire de la convention d'arbitrage. Enfin, les mécanismes du Code civil servent efficacement à neutraliser les effets du principe de relativité de la convention d'arbitrage. Il s'agit notamment de la bonne foi, du mandat, de la stipulation pour autrui et de la cession. Arbitration as an institution based on the intention of the parties, the consent on the multi-party arbitration procedure raises many problems relating to the way in which the parties express their intention to participate in a unique arbitration forum. This study aims to determinate the manner in which the arbitrator can join disputes resolution involving the groups of companies. The normal way to get a multi-party procedure is to provide it in an arbitration clause. This can be by signing a single arbitration agreement by all the parties involved. In certain cases, the multi-party arbitration can also be possible with several arbitration agreements especially when the parties took part in carrying out ofthe same economic operation. However, in other situations, the multi-party arbitration procedure is unrelated to consent. A non-signatory party can nevertheless be bound by an arbitration agreement signed by an other party. To allow the participation in the arbitration procedure of a third party non-signatory of the arbitration agreement, the arbitrators use several concepts provided chiefly by the national laws. 80, the lifting of the corporate veil, the doctrine of economic reality and estoppel, are the best tools for the arbitrators to bring to the arbitration procedure, by force or on request, a non-signatory of the arbitration agreement. Lastly, the mechanisms of the Civil code are used with efficiency by arbitrators to neutralize the effects of the relativity principle of the arbitration agreement. Those mechanisms are in particular the good faith, mandate, stipulation for another and assignment.
Keywords: Arbitrage; Arbitragem; Arbitration; Convention d'arbitrage; Effets (extension); Extension of the arbitration clause; Groupes de sociétés; Groups of Companies; Third Party non-signatory; Tierces parties non-signataires

The Role of International Arbitrators - Franck, Susan D. (ILSA Journal of International & Comparative Law, 2006)

The Contractarian Model of Arbitration and Its Implications for Judicial Review of Arbitral Awards - Kirgis, Paul F. (Oregon Law Review, 2006)

Harmonizing Business Laws in Africa: Ohada Calls the Tune - Dickerson, Claire Moore (Columbia Journal of Transnational Law, 2005)
OHADA (in English, Organization for Harmonization in Africa of Business Laws) is a system of business laws and implementing institutions. Sixteen West African nations adopted this regime in order to increase their attractiveness to foreign investment. Because most of the member states are former French colonies, the OHADA laws are based on the French legal system. Despite certain economists’ recent, well-publicized assertions that any French-based legal system is incompatible with development, other studies challenge those claims and in doing so outline characteristics that a pro-development system of business laws should possess. This Article reviews selected provisions from OHADA’s corporate law and of OHADA’s institutions, revealing that they correspond to those pro-development characteristics. Interviews conducted with legal professionals in Senegal, Côte d’Ivoire, and Cameroon highlight the local perception that the OHADA regime, while still
Keywords: Africa; Claire Moore Dickerson; Harmonizing Business Laws; OHADA; SSRN

L'arbitrage et la distribution commerciale - Jardin, Laurent du; Erauw, Johan; Hollander, Pascal; Keutgen, Guy; Matra, Didier; Van Houtte, Hans (Actes du colloque du CEPANI du 17 novembre 2005, 2005)

O processo de composição do Tribunal arbitral internacional e o seu funcionamento - Vescovi, Luiz Fernando (Espaço Jurídico Journal of Law, 2005)
O presente trabalho vem a delinear, sob forma objetiva, o efetivo escopo de um Tribunal Arbitral, ponderando as suas características e o comprometimento com as partes que a elegem. Apresenta o procedimento e o processo de como se constitui um tribunal dessa espécie, assim como as vantagens existentes quando da sua utilização. Enfatiza, de plano, a escolha dos apreciadores do juízo arbitral, assim como a análise circunstancial sobre a incidência da Lei de Arbitragem brasileira à luz do Direito supranacional. Enaltece a viabilidade jurídica (segurança e validade) que o instituto arbitral expressa, concernente às disposições principiológicas que dele decorrem. Ainda, descreve, de maneira esmiuçada, a forma de como o Tribunal Arbitral se compõe, sua competência, prerrogativas, e finalidades, bem como do funcionamento efetivo, no plano do Direito Internacional Privado.
Keywords: Composição; Direito Internacional Privado; Tribunal Arbitral

L'intervention du juge canadien avant et durant un arbitrage commercial international - Bachand, Frédéric (Université de Montréal ; Université Paris 2, 2004)
Cette thèse précise les conditions dans lesquelles les tribunaux judiciaires canadiens peuvent intervenir avant ou durant un arbitrage commercial international, soit afin d'y prêter assistance, soit afin d'en contrôler la légalité. Elle soumet également ces conditions à l'analyse critique, dans le but d'esquisser une théorie générale de l'intervention avant et durant un arbitrage commercial international des juges oeuvrant dans les États qui ont choisi d'accorder leur concours à la justice arbitrale internationale. Principalement, cette théorie repose sur l'idée selon laquelle l'intervention judiciaire survenant avant le prononcé de la sentence ne doit - à quelques exceptions près - servir que les intérêts des opérateurs du commerce international, les intérêts publics prépondérants ne devant être pris en compte que dans l'élaboration des conditions de l'intervention judiciaire survenant après le prononcé de la sentence. De cette idée directrice découlent deux conséquences majeures. D'abord, les ordres juridiques des États qui accordent leur concours à la justice arbitrale internationale doivent être perméables à des faits normatifs transnationaux qui s'intéressent à l'intervention judiciaire avant et durant un arbitrage commercial international, car l'adoption d'une loi ayant vocation à régir spécialement l'arbitrage commercial international ne peut jamais - à elle seule - assurer que les tribunaux judiciaires agiront de manière pleinement satisfaisante. Ensuite, les conditions de cette intervention doivent surtout avoir pour objectif d'accroître l'efficacité - envisagée du point de vue des opérateurs du commerce international - de ce système de justice internationale. This thesis sets out the conditions under which Canadian courts can intervene prior to and during an international commercial arbitration, either to assist the arbitral process or to control its legality. These conditions are also analyzed in a critical manner, with a view to elaborating a general theory of judicial intervention prior to and during an international commercial arbitration in States that have chosen to support international arbitral justice. This theory essentially rests on the idea that judicial intervention occurring before the rendering of the award must almost entirely be geared towards satisfying the interests of international business operators, as superior public interests need only be reflected in the conditions under which courts may intervene after an award has been rendered. Two major consequences flow from this idea. Firstly, the legal orders of States that have chosen to support international arbitral justice must be permeable to transnational normative facts which relate to judicial intervention prior to and during an international commercial arbitration, as the adoption of legislation dealing specifically with international commercial arbitration can never - in itself - ensure that courts will act in a fully satisfactory manner. Secondly, the conditions of such intervention must essentially be aimed at increasing the efficiency - assessed from the point of view of international business operators - of this system of international justice.
Keywords: Arbitrage commercial international; Arbitration; Canadian law; Civil procedure; Comparative law; Droit canadien; Droit comparé; Droit international privé; Droit judiciaire privé; International commercial arbitration; Intervention judiciaire; Judicial intervention; Loi type de la CNUDCI; Private international law; UNCITRAL Model Law

Qui contrôle l’arbitrage ? : autonomie des parties, pouvoirs des arbitres et principe d’efficacité - Kaufmann-Kohler, Gabrielle (Liber amicorum Claude Reymond : autour de l'arbitrage, 2004)

Conciliation et médiation judiciaires - Joly-Hurard, Julie (Droit privé, 2003)
Keywords: Concilition judiciaire; Médiation judiciaire; Pourparlers judiciaires

Les recours dilatoires contre les sentences arbitrales devant la Cour d'Appel de Paris (Analyse des décisions rendues entre janvier 1996 et décembre 2000) - Mantilla Espinosa, Fabricio (Estudios Socio-Jurídicos, 2003)
Este artículo está basado en el ensayo realizado en mayo de 2001, bajo la dirección de los doctores Jean de Hauteclocque y Christian Larroumet del departamento Contentieux et Arbitrage de la firma de abogados Lovells en París.

Essays on Bargaining with Outside Options - Adamuz Peña, Mercedes (Universitat Autònoma de Barcelona, 2002)
Los modelos de negociación con opciones exteriores normalmente suponen que los pagos de estas opciones son independientes de las acciones que los negociadores toman durante el proceso negociador. Sin embargo, en muchos contextos, la opción exterior depende de lo que las partes hagan durante la fase negociadora. Uno de estos contextos es el de aquellas negociaciones que se llevan a cabo en presencia de un árbitro. Esta tesis realiza algunas contribuciones a la teoría de la negociación con opciones exteriores, enfatizando aquellas situaciones donde las opciones exteriores aparecen por la intervención de árbitros. En el capítulo 2 analizo los efectos del arbitraje en las negociaciones cuando su uso es voluntario. Considero un modelo de negociación por concesiones donde las partes tienen la posibilidad de llamar a un árbitro con el consentimiento del oponente. Demuestro que la introducción del arbitraje distorsiona el resultado de la negociación. Esta distorsión depende de los costes relativos de implementar una partición mediante un proceso negociador versus un proceso arbitral. Si los costes del arbitraje son pequeños en relación a los costes de la negociación, entonces la partición negociada se aproxima a la propuesta por el árbitro, y en casos extremos el arbitraje es utilizado en equilibrio. Sin embargo, los jugadores no eligen siempre el método más eficiente de resolver su disputa: a veces negocian cuando es más eficiente acudir al arbitraje. En el capítulo 3 estudio los efectos de diferentes procedimientos arbitrales en el resultado de una negociación, en un modelo donde los jugadores realizan demandas no crecientes y el árbitro es llamado solo cuando las negociaciones se declaran rotas. Dos procedimientos arbitrales son analizados: el arbitraje convencional, donde el árbitro es libre de elegir su acuerdo y el arbitraje de oferta final, donde el árbitro está obligado a elegir una de las últimas ofertas de los jugadores. Demuestro que si los jugadores son suficientemente pacientes y el árbitro sigue un procedimiento de oferta final, en equilibrio, los jugadores negocian una partición pero toma algún tiempo llegar a ella. Sin embargo, si el árbitro sigue un procedimiento convencional, en equilibrio los jugadores utilizarán esta institución para resolver su disputa. Finalmente, en el capítulo 4 discuto el papel que juegan las opciones exteriores inciertas en las negociaciones cuando existe información incompleta acerca de su existencia. Examino una guerra de desgaste donde los jugadores disfrutan de información privada acerca de sus posibilidades de dejar la mesa de negociación para tomar una opción exterior. Hay dos tipos de jugadores: los tipos débiles, que no tienen opciones exteriores y prefieren conceder que salirse del juego, y los tipos fuertes que tienen opciones exteriores tales que prefieren salirse que conceder. El principal mensaje que surge del análisis de este juego es que la incertidumbre acerca de la posibilidad de que el oponente se vaya, mejora la eficiencia porque incrementa la probabilidad de concesión. Más precisamente, si la probabilidad de que el oponente sea fuerte es relativamente alta, la negociación acaba con una concesión segura. En el otro extremo, si la probabilidad de que el oponente sea débil es alta, los tipos fuertes dejarán en algún momento el juego con probabilidad igual a 1, dejando a los débiles jugando, desde ese momente en adelante el ineficiente equilibrio de la guerra de desgaste clásica. Incluso en este caso, la probabilidad de concesión a lo largo de la fase de incertidumbre del juego se incrementa.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Ciències Socials; Conventional arbitration; Final-offer arbitration; Negociación; Opciones exteriores

L’arbitrage international en Afrique : quelques observations sur l’OHADA - Boivin, Richard; Pic, Pierre (Revue générale de droit, 2002)
Avec le Traité relatif à l’Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) de 1993, l’Acte uniforme relatif au droit de l’arbitrage et le Règlement d’arbitrage de la Cour commune de justice et d’arbitrage (CCJA) de 1999, l’arbitrage international a fait une entrée remarquée en Afrique francophone. Dans cet article, les auteurs esquissent une vue d’ensemble du fonctionnement et des mécanismes de l’arbitrage OHADA.
Keywords: Arbitrage; Arbitrage international; Arbitragem; Arbitration; International Arbitration; OHADA

Les sociétés et l'arbitrage - Caprasse, Olivier (Bruylant, 2002)

Les modes alternatifs de règlement des conflits - Rivier, Marie-Claire; Ancel, Pascal; Blanc, Gérard; Cottin, Marianne; Gout, Olivier; Haubry, Xavier; Lawson-Body, Latékoué; Pourret, Jean-Louis; Sayn, Isabelle (Mission de recherche droit et justice, 2001)
La recherche effectuée a conduit à examiner comment les modes alternatifs de règlement des conflits (MARC), a priori nouveaux dans le droit français, ont été intégrés dans le discours des juristes, tel que tenu dans un ensemble de publications sélectionnées. Le dépouillement a permis l'établissement de 88 fiches concernant les ouvrages, et de 336 fiches s'agissant des revues. L'étude de cette masse documentaire, représentative du réseau de publications par lesquelles les juristes présentent, analysent le droit et contribuent à le faire, a montré comment la formule de "modes alternatifs" est entrée dans le discours doctrinal, mais aussi l'hétérogénéité des termes et des sens que recouvre cette formule. Quant au contenu du discours, on constate des constantes (un discours "de mode" et un discours "de crise") et des variantes dans l'appréciation portée sur cet objet. Loin de voir dans le développement des modes alternatifs de règlement des conflits une raison de remettre en cause leur activité et leur rôle, les juristes français ont intégré cet objet, recouvrant pour l'essentiel des mécanismes juridiques classiques, dans leurs analyses, et pour chacun des secteurs du droit concerné, l'ont situé dans un débat préexistant. La recherche de définitions, la (re)construction de catégories juridiques, l'élaboration d'un régime, sont autant de questions aujourd'hui considérées comme part intégrante de toute présentation de la justice ou des appareils judiciaires. Le discours tenu par les juristes tend aujourd'hui à privilégier l'examen technique de questions, situées dans le contexte d'une évolution caractérisée par la contractualisation, la procéduralisation du droit. Cette évolution, et non révolution, est désormais, dans la majorité des cas, présentée comme un phénomène irréversible.

Procedural detachment in international commercial arbitration : the law applicable to arbitral procedure - Petrochilos, Georgios (University of Oxford, 2000)
This thesis seeks to ascertain the rules of private international law determining the procedural law of international commercial arbitral proceedings. In an Introduction, the author outlines the fundamental notions, introduces the topic and the major doctrines and issues, and sets out his methodology and structure of the work. The thesis examine first, as a preliminary issue, the considerations influencing the assumption of jurisdiction over arbitral proceedings. Chapter 1 discusses the various theories on the lex arbitri (the law supplying the general legal framework of an arbitration) as relevant to the procedural law, and concludes that they are deductive and therefore unable to satisfactorily to determine the applicable procedural law. Chapter 2 analyses major national laws as case-studies of the technique and scope of application of international arbitration law, and suggests a model of legislative and court jurisdiction based on the legal concept of 'seat of the arbitration' and on considerations based on the most appropriate court to control an arbitration. Chapter 3 discusses the obligations of the state of the seat under the European Convention on Human Rights and confirms the findings in Chapter 2. In a second part, the thesis elaborates on the title and extent of permissible municipal law interference. Chapter 4 tests the validity of the propositions derived from Chapters 2 and 3 against arbitral practice and concludes that seldom will arbitrators derogate from the law of the seat. Chapter 5 examines the particular case of arbitrations with states and similar entities. The third part discusses the relevance of compliance with the law of the seat at the stage of enforcement of an award. Chapter 6 deals with the technical issue of whether annulment at the place of making precludes enforcement in other fora. That chapter gives the opportunity to discuss models of separation of international jurisdiction and co-operation between different jurisdictions from a practical perspective. It thus serves as a convenient introduction to Chapter 7, which discusses the more abstract question of the nexus required between an arbitral award and the municipal law of the state of rendition in order for the award to enter, in limine, the scope of application of the international instruments in the field. The thesis ends with Conclusions in the form of model provisions for municipal law and arbitration rules.
Keywords: Arbitrage; Arbitragem; Arbitration; International commercial arbitration; Procédure arbitrale